Mental Representation and Access of Polymorphic Words in Bangla: Evidence from Cross-modal Priming Experiments - Dasgupta, Tirthankar; Choudhury, Monojit; Bali, Kalika; Basu, Anupam (In Proceedings of ICON-2010, Kharagpur, India, 2010)
We conduct a cross-modal priming experiment to determine the mental representation and access strategies for morphologically derived words in Bangla. Analysis of reaction time and error rates indicates that morphologically related words trigger priming effects, even when they are phonologically opaque, and phonologically related but morphologically unrelated words do not exhibit priming. Thus, there is a strong evidence for morphological decomposition of derivationally suffixed words in the minds of the Bangla speakers, though certain suffixes do not seem to evoke decomposition rules. We also observe that word recognition time is also strongly affected of certain orthographic features.